Handbook of Tourism and Quality-of-Life Research 2011
DOI: 10.1007/978-94-007-2288-0_17
|View full text |Cite
|
Sign up to set email alerts
|

Quality-of-Life and Travel Motivations: Integrating the Two Concepts in the Grevillea Model

Abstract: Over the past three decades, two bodies of literature have developed relatively independently: Quality of Life research in Psychology and Travel Motivations research in Tourism. Yet, the constructs underlying these two bodies of research are strongly interrelated. This book chapter: (1) reviews the Quality of Life research area with a specific focus on the role of vacations as a Quality of Life domain; (2) reviews prior work in the area of Travel Motivations with a specific focus on motivational segments which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 57 publications
0
19
0
3
Order By: Relevance
“…In recent years, SWB, or QOL, has received increasing attention in tourism research (e.g., Chancellor, Yu, & Cole, 2011;Dolnicar et al, 2012Dolnicar et al, , 2013McCabe, Joldersma, & Li, 2010;Nawijn, 2011;Neal et al, 2007;Sirgy, 2010;Sirgy, Kruger, Lee, & Yu, 2011). Similarly, in the literature of social marketing, SWB and QOL have been studied as key factors to evaluate business success (Dagger & Sweeney, 2006).…”
Section: Effects Of Service Evaluation Constructs On Tourist Swbmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, SWB, or QOL, has received increasing attention in tourism research (e.g., Chancellor, Yu, & Cole, 2011;Dolnicar et al, 2012Dolnicar et al, , 2013McCabe, Joldersma, & Li, 2010;Nawijn, 2011;Neal et al, 2007;Sirgy, 2010;Sirgy, Kruger, Lee, & Yu, 2011). Similarly, in the literature of social marketing, SWB and QOL have been studied as key factors to evaluate business success (Dagger & Sweeney, 2006).…”
Section: Effects Of Service Evaluation Constructs On Tourist Swbmentioning
confidence: 99%
“…Parallel to the economic outcome of tourism development (Dagger & Sweeney, 2006;Zeithaml, 2000), socio-psychological benefits and outcomes of tourism development have recently attracted increasing attention from researchers. Studies following this trend include those on tourist QOL (Andereck & Nyaupane, 2011;Dolnicar et al, 2012Dolnicar et al, , 2013Neal et al, 2007), tourist SWB (Filep, 2012;Gilbert & Abdullah, 2004;McCabe & Johnson, 2013), daily happiness during vacation (Nawijn, 2011), corporate social responsibility in tourism (Sheldon & Park, 2011), among others. Comparatively, tourist SWB could be singled out as the best proxy to represent the sociopsychological benefit of tourism on tourists.…”
Section: Effects Of Service Evaluation Constructs On Tourist Satisfacmentioning
confidence: 99%
See 1 more Smart Citation
“…From a multidimensional perspective, overall life satisfaction is functionally related to satisfaction within a number of an individual's life domains (Lee & Sirgy, 1995). In other words, QoL is an umbrella concept that refers to all aspects of a person's life including physical health, psychological well-being, and social well-being (Dolnicar, Lazarevski, & Yanamandram, 2012). For instance, Meeberg (1993, p. 37) defined QoL as ''a feeling of overall life satisfaction, as determined by the mentally alert individual whose life is being evaluated.''…”
Section: Quality Of Life (Qol)mentioning
confidence: 99%
“…Given the large number of motivational studies in travel and tourism, Dolnicar, Lazarevski, and Yanamandram (2012) carried out a review of literature on studies published in three major international tourism research journals: Tourism Management, Journal of Travel Research, and Annals of Tourism Research. Their research found that most articles related to tourist motivations and their effect on purchase decisions (Park & Yoon, 2009), with a few including motivations theories (Beh & Bruyere, 2007;Dann 2001;Iso-Ahola, 1982;Moreno Gil & Ritchie, 2009).…”
Section: Travel Motivationmentioning
confidence: 99%